Renal denervation in patients with resistant hypertension-assessment by 3T renal 23Na-MRI: preliminary results - Budjan, Johannes; Benck, Urs Tobias; Lammert, Alexander; Meyer, Melissa; Mircheva, Miryana; Diehl, Steffen J.; Konstandin, Simon; Schad, Lothar R.; Krämer, Bernhard; Schönberg, Stefan; Haneder, Stefan (In vivo, 2016)
Background/Aim: Renal denervation (RDN) has been considered a promising therapy option for patients suffering from therapy-resistant hypertension. Besides, in blood-pressure regularization, the kidneys play a fundamental role in sodium (23Na) homeostasis. This study assesses the effect of RDN on renal 23Na concentration using 23Na magnetic resonance imaging (MRI). Patients and Methods: Two patients with therapy-resistant hypertension underwent RDN. 23Na-MRI, 1H-MRI, including diffusion weighted imaging (DWI), as well as endothelial dysfunction assessment, were performed 1 day prior, as well as 1, 30 and 90 days after RDN. Results: The renal corticomedullary 23Na gradient did not change after RDN for all time points. Additionally, functional imaging and retinal vessel parameters were not influenced by RDN. Results regarding blood pressure changes and arterial stiffness, as well as patients' clinical outcome, were heterogeneous. Conclusion: RDN does not seem to alter renal 23Na concentration gradients, as measured by MRI.